Bored Out of Their Minds: The Detrimental Effects of No Child Left Behind on Gifted Children - Elizabeth A. Siemer (Washington University Journal of Law & Policy, 2009)
This Note will first discuss the histories of gifted education practice, federal gifted education policies, and No Child Left Behind, and the impact of No Child Left Behind on gifted education and address proposals for modifications to No Child Left Behind to improve gifted and talented education policies and perceptions nationwide.
Keywords: Educational change; Education & state; Gifted children; United States. No Child Left Behind Act of 2001; State aid to education